ANAlISIS PENGUKURAN KINERJA KARYAWAN DENGAN METODE HUMAN RESOURCES SCORECARD DI BMT LOGAM MULIA (Equilibrium: Jurnal Ekonomi Syariah, 2015)
Human Resources Scorecard (hRSC) is a method of measuring human resources in detail. This method measures the human resources of the four perspectives namely; financial, customer, operations and strategy. This article aims to measure the performance of employees with methods hRSC. Data obtained from the documentation and interviews and analyzed by hRSC from various perspectives. Kajin results showed that from the perspective of the financial performance of the employees KSPS BMT “X” in 2013 amounted to 2:17 (less categories) and in 2014 amounted to 3:17 (both categories). And from the perspective of customers in 2013 amounted to 3 (medium category) and in 2014 amounted to 3.79 (both categories). While operating perspective in 2013 amounted to 3:18 (medium category) and in 2014 by 4 (both categories). When the perspective of the strategy in the year 2013 by 3 (medium category) and in 2014 amounted to 3.88 (both categories). And comprehensively by looking at four hRSC overall perspective is generated, in the year 2013 by 3:01 (medium category) and in 2014 amounted to 3.85 (both categories).      Human Resources Scorecard (hRSC) merupakan sebuah metode  pengukuran  sumber  daya  manusia  secara  detail.  Metode ini mengukur sumber daya manusia dari empat perspektif yaitu; financial, pelanggan, operasi dan strategi. Artikel ini bertujuan untuk mengukur kinerja karyawan dengan metode hRSC. Data diperoleh dari dokumentasi dan wawancara dan dianalisis dengan metode hRSC dari berbagai perspektifnya. hasil kajin menunjukkan bahwa dari perspektif financial kinerja karyawan KSPS BMT “X” tahun 2013 sebesar 2.17 (kategori kurang) dan tahun 2014 sebesar 3.17 (kategori baik). Dan dari perspektif pelanggan pada tahun 2013 sebesar 3 (kategori sedang) dan tahun 2014 sebesar 3.79 (kategori baik). Sedangkan perspektif operasi pada tahun 2013 sebesar 3.18 (kategori sedang) dan tahun 2014 sebesar 4 (kategori baik). Manakala perspektif strategi di tahun 2013 sebesar 3 (kategori sedang) dan tahun 2014 sebesar 3.88 (kategori baik). Dan secara komprehensif dengan melihat empat perspektif hRSC secara menyeluruh dihasilkan, pada tahun 2013 sebesar 3.01 (kategori sedang) dan tahun 2014 sebesar 3.85 (kategori baik).